1989
DOI: 10.1289/ehp.8982171
|View full text |Cite
|
Sign up to set email alerts
|

Results of animal studies suggest a nonlinear dose-response relationship for benzene effects.

Abstract: Considering the very large industrial usage of benzene, studies in risk assessment aimed at the evaluation of carcinogenic risk at low Ievels of exposure are important. Animal data can offer indications about what could happen in humans and provide more diverse information than epidemiological data with respect to doseresponse consideration. We have considered experiments investigating metabolism, short·term genotoxicity tests, DNA adduct formation, and carcinogenicity long-term tests. According to the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…The relationship between adduct formation to DNA, saturation of benzene metabolism at the upper doses (in RNA, and protein of the assayed organs and benzenethe 10-100 ppm range), as previously discussed by Grilli administered dose stayed linear within a wide range of et al (2) and confirmed by Parodi et al (11). The satura-dosages less than 48.6 mg/kg.…”
Section: Cnd Not Determined (Lost By Accident)supporting
confidence: 73%
“…The relationship between adduct formation to DNA, saturation of benzene metabolism at the upper doses (in RNA, and protein of the assayed organs and benzenethe 10-100 ppm range), as previously discussed by Grilli administered dose stayed linear within a wide range of et al (2) and confirmed by Parodi et al (11). The satura-dosages less than 48.6 mg/kg.…”
Section: Cnd Not Determined (Lost By Accident)supporting
confidence: 73%